(untitled) (Perner’s Contacts, 2019)
Inland waterway freight transport mainly uses oil and petrol from petroleum products. In the territory of Slovakia, the Danube river is used as a transport route with a dock in Bratislava, by means of which barges transport goods to foreign ports. The advantage of using this mode of transport is low environmental burden and also the price for transport. The disadvantages include dependence on natural conditions (water level) and transport time.